Early and Late Pregnancy Complications in Women Who Experience First Trimester Vaginal Bleeding at Tertiary Care Hospital, Karachi - Sadia, .; Majid, Erum; Sultan, Kainat; Manzoor, Mahrukh; Ali, Sidra; Komal, . (Biological and Clinical Sciences Research Journal, 2025)
First trimester vaginal bleeding is a common obstetric presentation and a potential predictor of adverse pregnancy outcomes. Timely identification and management are essential to mitigate risks for both mother and fetus, particularly in resource-constrained settings. Objective: To determine the maternal and fetal complications in patients presenting with first trimester vaginal bleeding at a tertiary care hospital. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Jinnah Postgraduate Medical Centre (JPMC), Karachi, over six months from May 2023 to October 2023, following ethical approval. A total of 145 pregnant women aged 20–45 years, presenting with vaginal bleeding within the first 12 weeks of gestation, were recruited using non-probability consecutive sampling. Women with systemic illness, bleeding disorders, or malignancy were excluded. Detailed demographic data and obstetric history were collected, and all participants were followed until delivery. Maternal outcomes assessed included miscarriage, term/preterm delivery, placenta previa, placental abruption, pre-eclampsia, and delivery-related complications. Fetal outcomes evaluated were low birth weight, intrauterine growth restriction (IUGR), congenital anomalies, prematurity, and stillbirth. Data were analyzed using SPSS version 20. Chi-square test was used to determine associations with booking status, with p ≤ 0.05 considered statistically significant. Results: Out of 145 participants, 56 (38.6%) experienced miscarriages, while 28 (19.3%) had preterm and 66 (45.5%) had term deliveries. Placenta previa and placental abruption were noted in 9 (6.2%) and 6 (4.1%) cases respectively. Caesarean section was performed in 43 (29.7%) patients, with instrumental delivery and postpartum haemorrhage reported in 4 (2.8%) and 6 (4.1%) cases respectively. Fetal complications included low birth weight in 24 (16.6%), prematurity in 27 (18.6%), IUGR in 16 (11.0%), congenital anomalies in 6 (4.1%), and stillbirth in 3 (2.1%) neonates. Unbooked patients showed significantly higher rates of miscarriage and preterm birth (p < 0.05). Conclusion: First trimester vaginal bleeding is associated with a considerable risk of adverse maternal and fetal outcomes, particularly among unbooked patients. Early detection, consistent antenatal care, and vigilant monitoring are imperative to improve pregnancy prognosis.